Entrepreneurship among People with Disabilities in Unstable Macroenvironment Conditions - Koza, Andrzej; Politaj, Adriana (Przedsiębiorczość osób z niepełnosprawnością w warunkach niestabilnego makrootoczenia, 2024)
Aim: The study attempted to characterise and identify the behaviour of people with disabilities operating as self-employed entrepreneurs in the period of dynamic changes in the macroenvironment related to the outbreak of the COVID-19 pandemic and the war in Ukraine. Methodology: The authors aimed to identify the factors affecting changes in self-employment among people with disabilities, and to place them in the context of the changes occurring in the macroenvironment. In particular, the subject of the research was to determine the trends in self-employment among people with disabilities against the background of the total population aged 15 years or older, as shown in research into the economic activity of the population in the context of selected macroeconomic parameters. For the purposes of the paper, the following research hypothesis was formulated: Self-employment among disabled people is a good alternative to full-time employment in unstable macroenvironmental conditions, because it is better adapted to their capabilities and gives them greater freedom in shaping their working time. The basic research question was whether the situation of disabled people on the labour market depends on changes in the macroenvironment, and if self-employment is a better form of activity on the labour market than working full-time? The adopted research methods were: critical analysis of the literature, statistical analysis, the inductive method, and dependency analysis based on Pearson’s correlation coefficient. Results: The subject research hypothesis was verified only with regard to some self-employed people with significant and medium disabilities. However, in terms of all self-employed people with disabilities, the hypothesis must be rejected. The basic time scope of the research covered the years 2019-2022 and the first quarter of 2023, and allowed for comparisons of the behaviour of disabled people in conditions of turbulence caused by the COVID-19 pandemic and the war in Ukraine, with macroeconomic conditions unaffected by those two factors. The research included self-employed people with disabilities listed in the register of the National Fund for the Rehabilitation of People with Disabilities (PFRON). Following the study of the literature and empirical research, the authors were unable to fully confirm the formulated hypothesis. Implications and recommendations: The authors pointed to the necessity of continuing the research process in the field of the behaviour of entrepreneurs with disabilities in conditions of an unstable macroenvironment. This study is an introduction to further discussion and considerations in this area and justifies the need to verify the adopted research assumption with the passage of time and the acquisition of new data. This will allow to avoid typical errors resulting from a relatively short time range of observations. Originality/value: The article is a response to the cognitive needs of disabled entrepreneurs in conditions of rapid macroeconomic change. There is a clear lack of findings in this area in the literature. This study was also intended to fill the existing gap in scientific research on the situation of people with disabilities in Poland and around the world.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 3, s. 13-27
Keywords: entrepreneurship; people with disabilities; self-employment; macroenvironment; przedsiębiorczość; osoby z niepełnosprawnością; samozatrudnienie; makrootoczenie